Effect of Au substrate and coating on the lasing characteristics of GaAs nanowires - Gyanan Aman (Nature Portfolio, 2021)
Abstract Optically pumped lasing from highly Zn-doped GaAs nanowires lying on an Au film substrate and from Au-coated nanowires has been demonstrated up to room temperature. The conically shaped GaAs nanowires were first coated with a 5 nm thick Al2O3 shell to suppress atmospheric oxidation and band-bending effects. Doping with a high Zn concentration increases both the radiative efficiency and the material gain and leads to lasing up to room temperature. A detailed analysis of the observed lasing behavior, using finite-difference time domain simulations, reveals that the lasing occurs from low loss hybrid modes with predominately photonic character combined with electric field enhancement effects. Achieving low loss lasing from NWs on an Au film and from Au coated nanowires opens new prospects for on-chip integration of nanolasers with new functionalities including electro-optical modulation, conductive shielding, and polarization control.